2013
DOI: 10.7589/2013-01-024
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Toxoplasmosis in Wild Boar (Sus scrofa) and Identification of theToxoplasma gondiiTypes Involved

Abstract: ABSTRACT:Congenital toxoplasmosis has been little described in wild animals. We report a case of vertical transmission in wild boar (Sus scrofa). Necropsy and histopathologic examination of a pregnant female and her three fetuses revealed all to have lesions compatible with acute toxoplasmosis. Nested polymerase chain reaction B1 gene detected Toxoplasma gondii in maternal (heart and diaphragm) and fetal (central nervous system, retina, optic nerve, heart, lung, tongue, and diaphragm) samples. The mother had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 26 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…Calero-Bernal et al [14] reported similar findings in boars caused by T. gondii congenital infection: the pregnant mother carried less fetuses than those expected for this species and one of them presented bilateral anophthalmia, agenesis of the nasal cartilage and prognathism. Toxoplasmosis was diagnosed by PCR and histopathology in both maternal and fetal tissues [14].…”
Section: Discussionmentioning
confidence: 67%
“…Calero-Bernal et al [14] reported similar findings in boars caused by T. gondii congenital infection: the pregnant mother carried less fetuses than those expected for this species and one of them presented bilateral anophthalmia, agenesis of the nasal cartilage and prognathism. Toxoplasmosis was diagnosed by PCR and histopathology in both maternal and fetal tissues [14].…”
Section: Discussionmentioning
confidence: 67%
“…Wild boars are considered a good indicator species for environmental contamination with T. gondii because they are presumed to acquire the infection from contact with soil. However, wild boars are omnivorous animals and could be infected with all three infective forms of the parasite: sporozoites of oocysts that have sporulated in the environment after having been shed there in unsporulated form by felids; bradyzoites of tissue cysts, which are carried in the tissues of chronically infected hosts; and tachyzoites, which dominate in acute infections and may cause transplacental [ 23 ] and possibly galactogenic and venereal infections.…”
Section: Discussionmentioning
confidence: 99%
“…The observed C-score was calculated for each presence/absence matrix and compared with the expected C-score calculated for 5000 randomly assembled null matrices by Monte Carlo procedures. The analysis was carried out using the software EcoSim 7.72 [38] .…”
Section: Methodsmentioning
confidence: 99%